Optical and electron microscopy study of laser-based intracellular molecule delivery using peptide-conjugated photodispersible gold nanoparticle agglomerates. Issue 1 (December 2016) - Krawinkel, Judith; Richter, Undine; Torres-Mapa, Maria; Westermann, Martin; Gamrad, Lisa; Rehbock, Christoph; Barcikowski, Stephan; Heisterkamp, Alexander
Abstract Background Cell-penetrating peptides (CPPs) can act as carriers for therapeutic molecules such as drugs and genetic constructs for medical applications. The triggered release of the molecule into the cytoplasm can be crucial to its effective delivery. Hence, we implemented and characterized laser interaction with defined gold nanoparticle agglomerates conjugated to CPPs which enables efficient endosomal rupture and intracellular release of molecules transported. Results Gold nanoparticles generated by pulsed laser ablation in liquid were conjugated with CPPs forming agglomerates and the intracellular release of molecules was triggered via pulsed laser irradiation ( $$λ$$ λ = 532 nm, $$τ _{pulse}$$ τ p u l s e = 1 ns). The CPPs enhance the uptake of the agglomerates along with the cargo which can be co-incubated with the agglomerates. The interaction of incident laser light with gold nanoparticle agglomerates leads to heat deposition and field enhancement in the vicinity of the particles. This highly precise effect deagglomerates the nanoparticles and disrupts the enclosing endosomal membrane. Transmission electron microscopy images confirmed this rupture for radiant exposures of 25 mJ/cm $$^{2}$$ 2 and above. Successful intracellular release was shown using the fluorescent dye calcein. For a radiant exposure of 35 mJ/cm $$^{2}$$ 2 we found calcein delivery in 81 % of the treated cells while maintaining a high percentage of cell viability. Furthermore, cell proliferation and metabolic activity were not reduced 72 h after the treatment. Conclusion CPPs trigger the uptake of the gold nanoparticle agglomerates via endocytosis and co-resident molecules in the endosomes are released by applying laser irradiation, preventing their intraendosomal degradation. Due to the highly localized effect, the cell membrane integrity is not affected. Therefore, this technique can be an efficient tool for spatially and temporally confined intracellular release. The utilization of specifically designed photodispersible gold nanoparticle agglomerates (65 nm) can open novel avenues in imaging and molecule delivery. Due to the induced deagglomeration the primary, small particles (~5 nm) are more likely to be removed from the body.